Use of EP3533-Enhanced Magnetic Resonance Imaging as a Measure of Disease Progression in Skeletal Muscle of mdx Mice - Murphy, Alexander Peter; Greally, Elizabeth; O'Hogain, Dara; Blamire, Andrew; Caravan, Peter; Straub, Volker (Frontiers in Neurology, 2021)
Abstract As putative treatments are developed for Duchenne muscular dystrophy (DMD), sensitive, non-invasive measures are increasingly important to quantify disease progression. Fibrosis is one of the histological hallmarks of muscular dystrophy and has been directly linked to prognosis. EP3533 is a novel contrast agent with an affinity to collagen 1 that has demonstrated a significant and high correlation to ex vivo fibrosis quantification. Halofuginone is an established anti-fibrotic compound shown to reduce collagen skeletal muscle fibrosis in murine models of DMD. This experiment explored whether EP3533 could be used to detect signal change in skeletal muscle of mdx mice before and after a 12 week course of halofuginone compared to controls. Four age-matched groups of treated and untreated mice were evaluated: 2 groups of mdx (n=8, and n=13 respectively) and 2 groups of BL10 mice (n=5, and n=3 respectively). Treated mice received an intraperitoneal injection with halofuginone three times per week for 12 weeks, with the remaining mice being given vehicle. Both mdx groups and the untreated BL10 were scanned at baseline, then all groups were scanned on week 13. All subjects were scanned using a 7T Varian scanner before and after administration of EP3533 using a T1 mapping technique. Mice underwent grip testing in week 13 prior to dissection. Skeletal muscle was used for Masson’s trichrome quantification, hydroxyproline assay and immunofluorescent antibody staining. Untreated mdx mice demonstrated a significant increase in R1 signal from pre-treatment to post-treatment scan in three out of four muscles (gastrocnemius p=0.04, hamstrings p=0.009, and tibialis anterior p=0.01), which was not seen in either the treated mdx or the BL10 groups. Histological quantification of fibrosis also demonstrated significantly higher levels in the untreated mdx mice with significant correlation seen between histology and EP3533 signal change. Forelimb weight adjusted-grip strength was significantly lower in the untreated mdx group, compared to the treated group. EP3533 can be used over time as an outcome measure to quantify treatment effect of an established anti-fibrotic. Further studies are needed to evaluate the use of this contrast agent in humans.